Incidence of Lateral Prominence Pain Following Open Medial Displacement Calcaneal Osteotomy and the Efficacy of Crushplasty as a Preventive Technique. (October 2022) - Kim, Jaeyoung; Kim, Chul-Ho; Day, Jonathan; Seilern und Aspang, Jesse; Rajan, Lavan; Kumar, Prashanth
Background: There has been concern about lateral prominence pain at the osteotomy site following medial displacement calcaneal osteotomy (MDCO). However, no study has investigated this complication. This study aimed to investigate the incidence of lateral prominence pain following MDCO and examine the efficacy of crushplasty as a surgical technique to minimize this complication. Methods: This was a retrospective cohort study in which 137 patients (148 feet) who underwent MDCO were divided into 2 groups by whether they had concurrent crushplasty at the time of MDCO (crushplasty [n = 81] vs noncrushplasty group [n = 67]). Crushplasty was performed by flattening the bony step-off using a rongeur and bone impactor. Lateral prominence pain was defined as pain or irritating symptoms over the osteotomy site that persisted over 12 months after MDCO. The overall incidence of lateral prominence pain after MDCO and within each group was investigated. Multiple logistic regression analysis was used to determine the influence of possible risk factors on the development of postoperative lateral prominence pain. Results: The overall incidence of lateral prominence pain was 9.5% (14 of 148): 3.4% (3 of 87) in the crushplasty group, and 18% (11 of 61) in the noncrushplasty group, and χ 2 analysis showed a statistically significant relationship between crushplasty and lateral prominence pain ( P < .05). A relationship between the amount of medial displacement and the development of lateral prominence pain was observed in the noncrushplasty group (OR = 5.31, 95% CI 2.35-16.4, P < .05), but this was not observed in the crushplasty group ( P = .641). The amount of medial displacement was an independent risk factor for the development of lateral prominence pain (OR = 2.72, 95% CI 1.54-4.79, P < .05), and concurrent crushplasty had a negative relationship with lateral prominence pain development (OR = 0.12, 95% CI 0.03-0.57, P < .05). Conclusion: This study revealed that lateral prominence pain is a significant complication of MDCO, especially in the setting of a larger displacement. The crushplasty following MDCO may minimize this complication, particularly when a greater degree of hindfoot correction is attempted.